Diagnosis and clinical management of autism: implications for young children - Powell, Kelly K. (Henry Stewart Talks, 2022)
Symptoms of Autism Spectrum Disorder (ASD) in young children, How and when ASD symptoms emerge, Understanding early communication, interaction and language development, The foundational skills involved in promoting language and communication development, Current screening practices, Recommendations for early intervention, Empirically-supported interventions, Challenges families face and strategies to help